The Gorontalo Eco-Wise Initiatives (locowise) Desa Dunu Kabupaten Gorontalo Utara - Muh. Fakhri Jamaluddin; Dewi Sartika T. Zees; Sri Rahayu Ayuba (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
The Gorontalo Eco-Wise Initiatives (LOCOWISE) program in Dunu Village, North Gorontalo Regency, aims to preserve coastal ecosystems through reforestation and community empowerment. Reforestation activities are carried out along coastal areas, hilly regions, and residential zones by planting mangroves, fruit trees, and shade trees, which function to prevent coastal erosion, absorb carbon dioxide, and improve air quality. Additionally, the program provides education to the community on planting techniques, waste management, and composting, generating economic benefits while raising environmental awareness. Supporting facilities, such as thematic gardens, educational boards, and sustainable training, have been added to enhance aesthetics and promote tourism. By engaging the community as